Analisis Frekuensi Ciphertext dengan Algoritma Kriptografi DNA dan Transformasi Digraf - Faizah, Widya Nur; Khudzaifah, Muhammad; Ismiarti, Dewi (Jurnal Riset Mahasiswa Matematika, 2022)
DNA Cryptography is one of new algortihm in cryptography that is used to encrypt the data by converting the DNA code into binary code. Encryption process is expected to produce a random and unreadable ciphertext. This research aims to determine the result of encryption frequency analysis of the ciphertext obtained from the encryption process using DNA Cryptography and Digraph Transformation algorithm. The formation of a symmetric key is carried out for the encryption and decryption process in DNA Cryptography, and modular arithmetic in Digraph Transformation algorithm. The encryption process produces ciphertext in the form of letters and symbols because if involves the use of an ASCII table. Frequency analysis is done by comparing the frequency of occurence of letters in the ciphertext with frequency of occurence of letters in English. The conclusion for this research is that the ciphertext looks random, not easy to read, and hard to guess. For the future work, researcher can change the choice of binary code combinatory in DNA Cryptographic algorithms, increase the character vocabulary in the Digraph Transformation algorithm, and use various languages to code.